Kultur Indonesia dalam Lagu Battaman oleh Idol Grup Choutokkyu (Kajian Semiotika) - Rosalina Wahyu Riani; Umi Handayani; Ricky Darmawan (Prodi Sastra Jepang Universitas Ngudi Waluyo, 2024)
Music is a branch of art that utilizes sound or sound carriers to convey the works it produces. Although it may appear limited to vibrations or sounds, in reality, the art of music is closely related to human thoughts and emotions. Music has an artistic nature, where the definition of artistic in music is a product of thought transmitted through elements of vibration in the form of frequencies processed by the nerves in the mind into different components. These elements include sound, tone, melody, and pitch.Music encompasses a wide variety of streams or genres, each with its unique characteristics and cultural significance. One notable genre is Dangdut, which is an adaptation of the Malay music stream that has developed rapidly in Indonesia over time. Dangdut has become a significant part of Indonesian culture, often characterized by its rhythmic and melodious elements that appeal to a broad audience. The genre integrates traditional musical instruments with modern sounds, creating a distinctive and captivating style.From a semiotic study perspective, music is rich with signs and symbols that can be analyzed and interpreted. Semiotics, the study of signs and symbols and their use or interpretation, allows us to understand how music can convey meanings and emotions beyond the mere sounds. In society, music can influence various aspects of life, including cultural identity, social interactions, and personal expression.This research focuses on the semiotic analysis of Dangdut music, particularly its presence in Japanese-language songs. The study aims to explore how Dangdut elements are incorporated into these songs and how they convey elements of cheerfulness and joy. By examining the signs and symbols in the music, we can gain insights into how cultural elements are blended and how music serves as a medium for cross-cultural communication.Furthermore, this research highlights the role of music in society, emphasizing its power to bring people together and bridge cultural gaps. Dangdut music, with its lively and engaging rhythm, serves as an example of how music can transcend cultural boundaries and resonate with people from different backgrounds. Through this study, we aim to contribute to a deeper understanding of the cultural significance of music and its impact on human emotions and social interactions.